The impact of market factors on pricing policy (Economics and region, 2023)
Nowadays, business activity is subject to strict competitive struggle, which becomes a decisive factor in the pricing of building and manufacturing enterprises' products. Establishing a reasonable level of prices on the market for building materials becomes one of the main objective factors affecting the successful planning of organizations' work, including forecasting the effectiveness of pricing policies and understanding how the planned pricing system will solve the possibility of successful development and resistance to competitive policies. The article presents a methodology for creating pricing policies for construction and manufacturing companies and establishes the main objectives and tasks. The necessity of preliminary assessment of demand for a particular group of products to achieve the desired financial result is identified. Within the framework of this scientific research, a project for creating a calculation of building materials is presented, taking into account all components of the cost of production. The importance of the impact of competitors' market policies on pricing for their own range of goods is substantiated. Factors and methods of pricing are discussed, with particular emphasis on determining the final price of the product.
Keywords: pricing strategy; competitiveness; costing; direct costs; enterprise; pricing; profitability